Hubungan Kompetensi Sosial Guru Terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran PAI di SMAN 10 Tangerang - Ripana, Anggi; Nurdin, Nurdin; Zubairi, Zubairi; Risma, Nila (STAI Asy-Syukriyyah, 2023)
This research aims to determine the relationship between the implementation of prayer services and the results of learning fiqh in class XI IPA 2 MAN 1 Tangerang students and the hypothesis tested is that there is a relationship between the implementation of prayer services and the learning outcomes of Islamic religious education. This research was conducted using the Descriptive Survey method. The target population was all students in class XI MAN 1 Tangerang, totaling 329 students and spread across 9 study groups. The sample was taken using random sampling technique, namely 40 students. As the independent variable is the Implementation of Prayer Services, the related variable is the Fiqh Learning Outcomes. For the independent variable instrument (x) using a questionnaire spread with 20 questions and 5 possible answers, namely, always, often, sometimes, rarely and never. And the related variable (y) is taken from the results of the Mid-Semester II Examination. From the hypothesis results, the rcount is 0.915 and this result is greater than the rtable, both significant 5% = 0.312 and significant 1% = 0.403. So it can be concluded that this research has a positive and significant relationship between the implementation of prayer services and the results of learning fiqh for class XI IPA 2 MAN 1 Tangerang students so that the hypothesis proposed by the researcher is accepted. It is hoped that the results of this research will be useful for improving the quality of learning so that learning outcomes are relatively good, as well as being able to foster student motivation to participate in teaching and learning activities through more effective roles. Apart from that, the results of this research can be used as a reference by related installations in developing teachers in improving teaching competence.